Analisis Konflik Internal dan Eksternal dalam Novel Call It What You Want Oleh Alissa Derogatis - Maria Evelynsia Imanuela Koagouw; Stepahani Johana Sigarlaki; Garryn Christian Ranuntu (CV Edujavare Publishing, 2026)
This study aims to identify, analyze, and describe the types of conflict, the causes of conflict, and the effects of conflict found in the novel Call It What You Want. This research employs Stanton’s theory of conflict, using a descriptive qualitative method and the intrinsic approach proposed by Wellek and Warren. Based on the results of the data analysis, two types of conflict were identified: internal conflict and external conflict. Conflict is one of the essential elements that construct a story; therefore, this study focuses on examining both internal and external conflicts. The findings reveal that the internal conflicts experienced by Sloane, the main character, include conflicts of emotion, thought, and inner struggle. Meanwhile, the external conflicts involve disputes between Sloane and Ethan, Sloane and Jordan and Lauren, Sloane and Graham, and Sloane and Reese.